PENYULUHAN HUKUM MENUMBUHKAN JIWA ANTI NARKOBA PADA WARGA DESA DUAMPANUAE KECAMATAN BULUPODDO KABUPATEN SINJAI - Eril, Eril; Sutra, Sutra; Nazaruddin, Nazaruddin (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
In this paper aims to reveal the dangers of drugs at all age levels both adults, adolescents and even childre. The number of drug users in Indonesia continues to increase. The origin of the problem, much of what is happening today is caused by drugs,with various types of drug abuse, with this finally in the medical world or medicine is no longer used. This type of drung is often misused and can lead to dependence. There are several reasons for using drugs, namely, among others, to deal with stress, and or to have fun. The data analysis used is by analyzing various types of information collected from various mass media which is strengthened by using original sources in books that explain the dangers of drugs, the causes of drug abuse and efforts to overcome drug abuse. What will happen, the author shares that the contributing factors to drung abuse can be caused by family factors that pay less attention to their children, and environmental factors can also be very influential so that religious education can be used as a role model for someone so they are not entangled in drug abuse.